Hubungan antara Pengetahuan, Dukungan Keluarga dan Personal Hygiene dengan Perawatan Luka Perineum Masa Nifas di Wilayah Kerja Puskesmas Belida Darat Kecamatan Darat Kabupaten Muara Enim Tahun 2021 - Pratiwi Tri Lestari; Syarifah Ismed; Eka Afrika (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Perineal care is an effort to provide fulfillment of the need for comfort by nourishing the area between the two thighs which is limited between the anal canal and the external genitalia in women who have given birth to avoid infection. The prevalence of childbirth mothers who experience perineal rupture in Indonesia in the age group of 25-30 years is 24% and at the age of 32-39 years is 62%. In 2013 57% of mothers received perineal sutures (28% due to episiotomy and 29% due to spontaneous tears). To determine the relationship between knowledge, family support and personal hygiene with postpartum perineal wound care in The Working Area of the Belida Darat Health Center, Belida Darat District, Muara Enim Regency. This research is an analytical survey quantitative research with a cross sectional approach, namely research with observations in a period and research subjects are observed once during the study. The results of the chi-square statistical test of the knowledge variable obtained value = 0.002, personal hygiene variable obtained value = 0.023, and the family support variable obtained value = 0.025 this indicates there is a significant relationship between family support and perineal wound care in the Region Belida Darat Health Center in Belida Darat K . District Muara Enim Regency in 2021.